Proposed Digital Marketing Strategy for Muslim Women’s Fashion Brand (Arra Style) - Akbar, Roni (AIBPM Publisher, 2020)
Arra Style is a small and medium enterprise of women fashion brand in Indonesia initiated in November 2016, producing and selling Muslim women’s apparel. In 2019, along with the declining numbers of Tanah Abang visitors, the sales of Arra Style also decreased since the brand simply relied on sales of Tanah Abang in-store transaction and WhatsApp. To adapt to changing customer behavior, Arra Style needs to adopt the existing technology and implement digital marketing. By conducting interviews with the internal and external stakeholders, the author proposed digital marketing strategies through communication channel strategies and sales channel strategies. These strategies are based on the classification of customer journey through the 5A funnel.